A quantitative assessment of bone area increase due to ornamentation in the Crocodylia. (30th June 2015) - Clarac, François; Souter, Thibaud; Cornette, Raphaël; Cubo, Jorge; de Buffrénil, Vivian
ABSTRACT Bone ornamentation, in the form of highly repetitive motives created by pits and ridges, is a frequent feature on vertebrate skull roofs and osteoderms. The functional significance of this character remains a matter of controversy and speculation. The many diverging hypotheses proposed to explain it all share a common logical prerequisite: bone ornamentation should increase significantly the surface area of the bones that bear it. In order to test this assumption in the Crocodylia, we developed a method for quantifying the gain in area due to ornamentation using a three‐dimensional‐surface scanner. On crocodylian osteoderms, the gain in area can be up to 40%, and on the cranial table, it ranges between 10 and 32% in adult specimens (in both cases, it shows substantial differences between the adults of the various species included in the sample). Area gain on the snout is lesser (0–20% in adults), and more variable between species. In general, bone ornamentation is less pronounced, and results in fewer area gains in juvenile specimens. The main morphometric results yielded by this study are discussed in reference to the few comparative data available hitherto, and to the functional interpretations proposed by previous authors. J. Morphol. 276:1183–1192, 2015. © 2015 Wiley Periodicals, Inc.